Subacute ruminal acidosis in dairy cows - physiological background, risk factors and diagnostic methods - Kovács, Levente (Array, 2020)
According to the latest studies, the prevalence of subacute ruminal acidosis (SARA) is around 20% in early and mid- lactation dairy cows, generating annual losses in the United States of approximately USD 500 million to 1 billion. The diagnosis of SARA is still difficult due to lack of pathognomonic clues and the delayed appearance of certain clinical signs. Therefore, SARA remains neglected or even unrecognized in many dairy herds. SARA is characterized by daily episodes of low ruminal pH, when the pH remains in the range of 5.2 to 6 for a prolonged period due to the accumulation of short-chain fatty acids and insufficient rumen buffering. The causes of SARA are related to high-grain diets, such as feeding excessive amounts of non-structural carbohydrates and highly fermentable forages, and insufficient dietary coarse fibre. SARA is associated with the inflammation of several organs and tissues in dairy cows, and its main long-term health and economic consequences are the fluctuation of feed intake, reduced fibre digestion, depression of milk yield and milk fat content, gastrointestinal damage, diarrhoea, laminitis, liver abscesses, and lameness. The aim of this review is to summarize the information available on the physiological aspects, risk factors, prevalence and possible indicators of SARA in dairy cattle. Basedon the existing literature, rumenocentesis and the use of an oral stomach tube are reliable field techniques to detect SARA. Nowadays, improved field techniques allowing the continuous measurement of reticuloruminal pH are also available for better diagnosis of SARA. Wireless indwelling pH probes may become important tools for the continuous measurement of ruminal pH in the coming years.